2010
DOI: 10.1158/1055-9965.epi-10-0747
|View full text |Cite
|
Sign up to set email alerts
|

Oral Contraceptive Use and Breast Cancer: A Prospective Study of Young Women

Abstract: Background: Previous studies convincingly showed an increase in risk of breast cancer associated with current or recent use of oral contraceptives from the 1960s to 1980s. The relation of contemporary oral contraceptive formulations to breast cancer risk is less clear.Methods: We assessed lifetime oral contraceptive use and the specific formulations used among 116,608 female nurses ages 25 to 42 years at enrollment in 1989, and subsequently updated this information every 2 years. We related this information to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
124
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 26 publications
10
124
1
5
Order By: Relevance
“…Regarding other HC use, the results are mainly in line with previous research, with an elevated BC risk especially among the young women. A large prospective study of women aged 24-43 years concluded that current HC use carries an excess risk of BC [12]. Correspondingly, a casecontrol study by Rosenberg et al [13] suggested a positive association between current HC use and risk of BC, more specifically in cases diagnosed in the recent years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding other HC use, the results are mainly in line with previous research, with an elevated BC risk especially among the young women. A large prospective study of women aged 24-43 years concluded that current HC use carries an excess risk of BC [12]. Correspondingly, a casecontrol study by Rosenberg et al [13] suggested a positive association between current HC use and risk of BC, more specifically in cases diagnosed in the recent years.…”
Section: Discussionmentioning
confidence: 99%
“…The prospective Nurses' Health Study II concluded with a positive association between oral contraceptive use and the risk of BC [12], as did a case-control study in 2008 [13]. On the other hand, no increase in BC risk was found in a population-based case-control study [14].…”
Section: Introductionmentioning
confidence: 94%
“…This risk mainly concerns women of high risk group; f. ex. genetically loaded ones (Burkman et al, 2004;Hunter et al, 2010). The analysis of our research showed remarkable differences between Polish and Belgian students in individual knowledge on the effect of oral contraception to bring forth a breast cancer (p<0.000001).…”
Section: Discussionmentioning
confidence: 63%
“…The majority of the interrogated students of Medical University of Lublin (93.7%) favor an opinion that oral contraception can give rise to breast cancer, which did not share a half smaller group (46.7%) of KATHO students. The research showed a little higher risk for a cancerous disease to appear in women using oral contraception (Hunter et al, 2010). The research suggests the breast feeding to be one of the simplest and at the same time an effective way of protection against breast cancer; however, no sufficiently valid proof of a protective effect of this factor has been found so far (Collaborative Group on Hormonal Factors in Breast Cancer, 2002;Lodha et al, 2011;do Carmo França-Botelho et al, 2012;Faupel-Badger et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…and selectively blocks estrogen-mediated receptors in rats [7]. Moreover, the use of synthetic steroidal contraceptives has proven unsafe to the health of the user as they pose risk of side effects [8][9][10]. …”
mentioning
confidence: 99%